Fuzzy Based Pseudo Random Number Generator used for Wireless Networks - Sadkhan, Sattar B; Thamer, Sawsan K; Hassan, Najwan A (Al-Nahrain Journal of Science, 2013)
In this paper an adaptive fuzzy system is proposed, it generates the frequency hopping sequence for a spread spectrum communication system. The system learns rules from data and acts as Pseudo Random Number Generator (PRNG) .Thirty sample patterns are the input to Fuzzy PRNG, while the bandwidth is partitioned into number of frequency bins. Each bin used triangular membership function to analyze the input to fuzzy sets, encoding these as fuzzy rules. The input vector matches if-part of a fuzzy rule and fires that rule’s output fuzzy set. The fuzzy system tested with 100 and 1025 frequencies and compared it with three other types of PRNG, the fuzzy system had lower values and thus gives a more uniform spread than did the other methods. The fuzzy system was easier to change and harder to intercept.